Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Quantifying responses of concurrent PM2.5-O3 pollution to their precursors in the Yangtze River Delta megacity Cluster of China - Mingliang Ma; Mengjiao Liu; Mengnan Liu; Yihong Jiao; Fei Meng; Pingjie Fu; Jingxue Bi; Tongshuai Rong; Yangyang Liu; Yuqiang Wang; Huaqiao Xing (Environment, Development and Sustainability, 2026)

Trophic magnification of antibiotics in a coral reef food web from the South China Sea: Bioaccumulation, source apportionment, and human health risks - Sai Wang; Wen-Qing Liao; Hong-Jin Zhang; Tuan-Tuan Wang; Peng-Fei Xie; Xian Sun; Guang-Guo Ying; Bi-Xian Mai; Jian-Liang Zhao; Lei Xiang; Ju Zhang (Environmental Pollution, 2026)

Modelling phase-transition-driven gas dispersion resulting from supercritical CO2 pipeline leak in complex terrain - Xinhong Li; Changzhi Bi; Cheng Li; Hanyu Liu; Fei Shi; Peihua Liu; Ziyue Han (Process Safety and Environmental Protection, 2026)

Tectonic forcing and climate modulation on the evolution of aeolian sediment provenance from the northeastern Tibetan Plateau margin to the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Chuanying Zhu; Xueyu Yan; Ke Bi; Qiang Shu; Ping Zhang (Quaternary Science Reviews, 2026)

Assessing the impacts of reclaimed water replenishment on riverine aquatic biodiversity using environmental DNA metabarcoding - Fei Zhao; Tao Chen; Shujian Wu; Dong Chen; Yihua Xiao; Penghao Wei; Xuejun Bi; Yiwei Wang; Liqun Chen; Guo Li; Xueqing Shi; How Yong Ng (Journal of Environmental Management, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Source, transport and impact of biomass burning emissions in spring 2024 in Yunnan, China - Lihui Lv; Feng Xiang; Haitao Xie; Fei Qiu; Ying Pan; Zihuai Yi; Zenan Wang; Zhichao Liu; Limei Bi; Lu Zhao; Qianqian Sun; Shuai Wang; et al. (Journal of Environmental Sciences, 2026)

Invasions of alien plants pose unprecedented challenges to China’s nature reserves under climate change - Jia-Xin Wang; Rainer W. Bussmann; Fei Qin; Yun-Fen Liang; Bao-Cai Han; Hai-Yan Bi; Tian-Tian Xue; Sheng-Xiang Yu (Biodiversity and Conservation, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Design and activity validation of GABA-gated chloride channels allosteric modulators based on computational biology - Siyi Yang; Shuang Gao; Tiansong Li; Jinghu Bi; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

LightDTA: lightweight drug-target affinity prediction via random-walk network embedding and knowledge distillation - Xiaoyu Huang; Xiangpeng Bi; Nianwen Xing; Wenjian Ma; Huasen Jiang; Qing Cai; Weigang Lu; Fei Yang; Zhiqiang Wei; Shugang Zhang (Molecular Diversity, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Computational simulation assisted exploration of homogenization induced changes in potato protein secondary emulsions for 3D printing - Zhi-gang Huang; Peng-da Ma; Ao-xue Qie; Fei Gao; Chong-hao Bi; Qiu-yue Du (Innovative Food Science & Emerging Technologies, 2025)

Site-specific substitution strategy for poisoning-resistant of ZrCo-based hydrogen isotope storage alloys - Shunrui Xiao; Jiacheng Qi; Jiapeng Bi; Fei Chu; Qianwen Zhou; Xiulin Fan; Jiahuan He; Xingwen Feng; Huaqin Kou; Xuezhang Xiao; Tao Tang; Wenhua Luo; et al. (Chemical Engineering Journal, 2025)

Quantitative estimation of the spatiotemporal responses of PM2.5 and O3 synergistic pollution to precursors in the Chengdu-Chongqing City Group of China - Mingliang Ma; Yihong Jiao; Mengjiao Liu; Mengnan Liu; Fei Meng; Huaqiao Xing; Jingxue Bi; Yuqiang Wang; Tongwen Liu; Pingjie Fu (Air Quality, Atmosphere & Health, 2025)

Effect of three pectin fractions from muskmelon on the formation of volatile sulfur compounds produced from methionine-sugars Maillard reaction - Xin Pan; Shuang Bi; Yingying Xu; Yanpei Cai; Fei Lao; Jingya Ai; Wenjiang Dong; Jihong Wu (Food Chemistry, 2025)

Investigating the role of potato protein isolate in high internal phase emulsions for 3D printing ink applications - Chong-hao Bi; Ao-xue Qie; Fei Gao; Quan-lai Li; Bin Tian; Xiao-rong Sun (Food Hydrocolloids, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Association of GRM7 Polymorphisms with Bilateral Auditory Regions Glutamate and Coupling with Glutathione in ARHL Patients - Jing Wang; Fuyan Li; Fuxin Ren; Wen Ma; Yuxi Liu; Wenjing Zhang; Xi Li; Yanfei Bi; Qian Xin; Fei Gao (Molecular Neurobiology, 2025)

Precise A·T-to-G·C Base Editing in Banana - Shaoping Wu; Chunhua Hu; Haocheng Zhu; Jinxing Liu; Tongxin Dou; Fei Qin; Binhui Yin; Fangcheng Bi; Qiaosong Yang; Ganjun Yi (Journal of Plant Growth Regulation, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Ratiometric fluorescent nanoprobes based on lanthanide coordination polymers for visual intelligent detection of phosphate - Yongxin Li; Rongrong Zhou; Fei Xue; Ning Bi; Lina Zhang; Qianyang Li; Kai Shi; Jiang Wu; Lei Jia; Jun Xu (Chemical Engineering Journal, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

The role of urban green space morphology and threshold in cooling efficiency: Evidence from five cities, China - Shibo Bi; Zheng Tian; Yi Zhang; Fei Dai (Journal of Cleaner Production, 2025)

Deformation patterns and failure mechanism of rock slopes with fault fracture zone induced by over-excavation - Bensheng Chen; Fei Gan; Gang Zheng; Haizuo Zhou; Hong Wang; Jing Bi; Hongwei Liu; Yansen Huang (Earth Science Informatics, 2025)

Removal of ciprofloxacin by PAA-PAM hydrogel: Adsorption performance and mechanism studies - Man Gao; Mengmeng Sun; Jingtao Bi; Shizhao Wang; Xiaofu Guo; Fei Li; Jie Liu; Yingying Zhao (Journal of Water Process Engineering, 2025)

Effect of ultrasound intervention timing on the formation mechanism and emulsifying properties of chickpea protein isolate-citrus pectin complexes - Zhi-gang Huang; Guo-liang Zhang; Ao-xue Qie; Quan-lai Li; Chonghao Bi; Fei Gao (Food Chemistry, 2025)

Investigation of noncovalent interaction between chelate-soluble pectin from muskmelon and selected volatile during thermal processing using multiple spectroscopy and molecular dynamics - Xin Pan; Shuang Bi; Yingying Xu; Fei Lao; Xingfeng Guo; Zhijian Xiao; Jihong Wu (Food Chemistry, 2025)

Design and performance investigation of novel efficient photocatalysts PVP-modified PVDF/BiOBr photocatalytic membranes for wastewater treatment - Fei Bi; Zhemei Zheng; Rongrong Li; Ruiying Du; Li Zhao; Shanshan Xiao; Liyan Wang; Xiangting Dong (Chemical Engineering Journal, 2025)

Provenance of fine-grained Quaternary sediments in the Tengger Sandy Desert recorded by Sr-Nd isotopes and its linkage with Quaternary aeolian silts on the Chinese Loess Plateau - Yuxin Fan; Minmin Gao; Fei Wang; Qingsong Cai; Guangliang Yang; Chunlei Zong; Ke Bi; Xueyu Yan; Qiang Shu; Bowen Kong (Quaternary Science Reviews, 2025)

Energy-free and ultrafast nano pump of water - Chun Li; Dongdong Zhou; Fei Zheng; Yujuan Wang; Kedong Bi (Chemical Engineering Journal, 2025)

Quercetin alleviates neonatal hypoxic-ischaemic brain injury by rebalancing microglial M1/M2 polarization through silent information regulator 1/ high mobility group box-1 signalling - Zhaoyan Chen; Fei Ruan; Di Wu; Xiaoping Yu; Yaqing Jiang; Wei Bao; Haicheng Wen; Jing Hu; Haidi Bi; Liping Chen; Kai Le (Inflammopharmacology, 2025)

An experimental and kinetic modeling study on the ignition kinetics of a sustainable aviation fuel and its blends with a traditional RP-3 jet fuel - Quan-De Wang; Ping Zeng; Qian Yao; Jinhu Liang; Bi-Yao Wang; Fei Huang; Jian-Gang Liu; Zu-Xi Xia (Fuel, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Features of particle-phase PAHs from traffic emissions using tunnel measurement and urban roadside observation in China - Fei Gao; Zhitao Cai; Zhenyu Luo; Junchao Zhao; Songxin Zheng; Li Wang; Bi Chen; Kebin He; Huan Liu (Environmental Pollution, 2025)

Quality control and improvement of GNSS-IR soil moisture robust inversion model - Yijie Li; Linyu Luo; Fei Guo; Furong Yang; Tianyang Wang; Hang Gao; Xinyu Bi; Zhitao Zhang; Yifei Yao (Advances in Space Research, 2025)

Chickpea protein stabilized Pickering emulsions: As a novel mayonnaise substitute - Chong-hao Bi; Ao-Xue Qie; Yi Liu; Fei Gao; Tong Zhou (Journal of Food Engineering, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Allergenicity risk in animal-based food proteins: Source, dietary factors effect, allergen detection and processing modification methods - Yanxiang Bi; Changqi Liu; Fei Pan; Wenjun Peng; Xiaoming Fang; Huilian Che; Wenli Tian (Trends in Food Science & Technology, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

An alloying element screening method to design Zr2Co based alloys with superior disproportionation resistance - Yang Liu; Xuezhang Xiao; Zhiyi Yang; Fei Chu; Panpan Zhou; Jiapeng Bi; Tiao Ying; Xingwen Feng; Jiangfeng Song; Yan Shi; Changan Chen; Wenhua Luo; et al. (Chemical Engineering Journal, 2024)

Relevance and mechanism of STAT3/miR-221-3p/Fascin-1 axis in EGFR TKI resistance of triple-negative breast cancer - Lu-Lu Jin; Hua-Jun Lu; Jun-Kang Shao; Yan Wang; Shi-Ping Lu; Bi-Fei Huang; Gui-Nv Hu; Hong-Chuan Jin; Chao-Qun Wang (Molecular and Cellular Biochemistry, 2024)

Hydrodynamics of focused waves acting on netting that extends above the mean sea level - Qiu-Pan Chen; Chao Ma; Yun-Peng Zhao; Chun-Wei Bi; Hang-Fei Liu (Ocean Engineering, 2024)

Plasma-induced surface interactions of Pd/SrTiO3 catalyst for improved performance of photocatalytic degradation of toluene - Dongliang Gao; Bingwei Wang; Jingyue Bi; Fan Xue; Mifen Cui; Zhaoyang Fei; Lei Li; Xu Qiao (Journal of Environmental Chemical Engineering, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Contribution of freefall and rock mass structure to post-fragmentation spreading of rockslides - Zhiyuan Zhu; Yihan Wu; Yuzhang Bi; Lu Zheng; Fei Chen; Wei Wu; Hong Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Control mechanism of trichloroethylene back diffusion by microstructure in a low permeability zone - Chen Feng; Fei Liu; Erping Bi (Journal of Hazardous Materials, 2024)

3D reconstruction and characterization of cotton bolls in situ based on UAV technology - Shunfu Xiao; Shuaipeng Fei; Yulu Ye; Demin Xu; Ziwen Xie; Kaiyi Bi; Yan Guo; Baoguo Li; Rui Zhang; Yuntao Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Genomic and epigenetic characterization of the arsenic-induced oncogenic microRNA-21 - Haoyan Ji; Zhuoyue Bi; Aashna S. Pawar; Akimasa Seno; Bandar Saeed Almutairy; Yao Fu; Yiran Qiu; Wenxuan Zhang; Ziwei Wang; Chitra Thakur; Hongjuan Cui; Liqun Yang; et al. (Environmental Pollution, 2024)

An integrated linguistic Pythagorean fuzzy decision-making approach for risk analysis of offshore wind turbine - Jinfeng Li; Chencan Bi; Fei Gao; Weikai He (Ocean Engineering, 2024)

Tumor suppressive activity of AHR in environmental arsenic-induced carcinogenesis - Ziwei Wang; Yao Fu; Akimasa Seno; Zhuoyue Bi; Aashna S. Pawar; Haoyan Ji; Bandar Saeed Almutairy; Yiran Qiu; Wenxuan Zhang; Chitra Thakur; Fei Chen (Toxicology and Applied Pharmacology, 2023)

Ecological implications of plant clonality - Sergio R. Roiloa; Wei Xue; Bi-Cheng Dong; Fei-Hai Yu (Flora, 2023)

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Safety assessment of organic micropollutants in reclaimed water: Chemical analyses, ecological risk assessments, and in vivo endocrine-disrupting studies - Fei Zhao; Yinfei Hao; Qianru Xu; Zhineng Hao; Xinhui Li; Lihua Cheng; Dong Chen; Xueqing Shi; Yihua Xiao; Penghao Wei; Xuejun Bi (Science of The Total Environment, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Non-oxide supported Pt-metal-group catalysts for efficiently CO and toluene co-oxidation: Difference in water resistance and degradation intermediates - Fukun Bi; Shuting Ma; Bin Gao; Yang Yang; Lexun Wang; Fuhao Fei; Jingcheng Xu; Yuandong Huang; Minghong Wu; Xiaodong Zhang (Fuel, 2023)

Factors affecting aroma compounds in orange juice and their sensory perception: A review - Xin Pan; Shuang Bi; Fei Lao; Jihong Wu (Food Research International, 2023)

Shewanella subflava sp. nov., a novel multi-resistant bacterium, isolated from the estuary of the Fenhe River into the Yellow River - Bi Luo; Jing-Yun Su; Ya-Nan Wang; Li Guan; Kai-Shi Dong; Hui-Jing Niu; Shao-Fei Shen; Yi Li (Antonie van Leeuwenhoek, 2023)

Dependence assessment in human reliability analysis using the 2-tuple linguistic information and DEMATEL method - Fei Gao; Wenjiang Liu; Xu Mu; Wenhao Bi; An Zhang (Process Safety and Environmental Protection, 2023)

Bipolar membrane electrodialysis combined with ozone oxidation wet scrubbing to remove SO2 and NO from flue gas and achieve CO2 mineralization - Yingying Zhao; Yupeng Cheng; Tingting Zhang; Shizhao Wang; Xiaofu Guo; Junsheng Yuan; Zhiyong Ji; Jie Liu; Fei Li; Jing Wang; Jingtao Bi (Fuel, 2023)

Systematic optimization of the square arc angle aquaculture tank combining CFD methodology and multi-objective genetic algorithm - Hang-Fei Liu; Xiaozhong Ren; Boru Xue; Chun-Wei Bi; Yun-Peng Zhao; Ying Liu (Aquacultural Engineering, 2023)

Dynamic community detection considering daily rhythms of human mobility - Yuhui Zhao; Bi Yu Chen; Fei Gao; Xinyan Zhu (Travel Behaviour and Society, 2023)

Energy Evolution Characteristics of Sandstones During Confining Pressure Cyclic Unloading Conditions - Yu Zhao; Shuang Dang; Jing Bi; Chaolin Wang; Fei Gan; Jiashen Li (Rock Mechanics and Rock Engineering, 2023)

Dense nonaqueous phase liquids back diffusion controlled by biodegradation and heterogeneous sorption-desorption - Chen Feng; Fei Liu; Fuyang Huang; Linpeng Chen; Erping Bi (Journal of Cleaner Production, 2023)

Identification and validation of core microbes associated with key aroma formation in fermented pepper paste (Capsicum annuumL.) - Meilun Li; Xinxing Xu; Shuang Bi; Xin Pan; Fei Lao; Jihong Wu (Food Research International, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Dental follicle cells show potential for treating Parkinson’s disease through dopaminergic-neuronogenic differentiation - Fei Bi; Jie Xiong; Xue Han; Chao Yang; Xinghan Li; Guoqing Chen; Weihua Guo; Weidong Tian (Human Cell, 2022)

Integrative analysis of the pharmaceutical active ingredient and transcriptome of the aerial parts of Glycyrrhiza uralensis under salt stress reveals liquiritin accumulation via ABA-mediated signaling - Quan Bi; Hua Yao; Fei Wang; Dajun He; Wenbin Xu; Shuangquan Xie; Xifeng Chen; Yuxia Li; Hailiang Liu; Haitao Shen; Hongbin Li (Molecular Genetics and Genomics, 2022)
The aerial parts of Glycyrrhiza uralensis supply substantial raw material for the extraction of active pharmaceutical ingredients comprehensively utilized in many industries. Our previous study indicated that salt stress increased the content of active ingredients. However, the regulatory mechanism remains unclear. In this study, RNA-sequencing (RNA-seq) of the aerial parts of G. uralensis treated with 150 mM NaCl for 0, 2, 6, and 12 h was performed to identify the key genes and metabolic pathways regulating pharmacological active component accumulation. The main active component detection showed that liquiritin was the major ingredient and exhibited more than a ten-fold significant increase in the 6 h NaCl treatment. Temporal expression analysis of the obtained 4245 differentially expressed genes (DEGs) obtained by RNA-seq revealed two screened profiles that included the significant up-regulated DEGs (UDEGs) at different treatment points. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of these UDEGs identified phenylpropanoid metabolism and flavonoid biosynthesis as the most significantly enriched pathways in 2 h treated materials. Interestingly, the carotenoid biosynthesis pathway that is related to ABA synthesis was also discovered, and the ABA content was significantly promoted after 6 h NaCl treatment. Following ABA stimulation, the content of liquiritin demonstrated a significant and immediate increase after 2 h treatment, with the corresponding consistent expression of genes involved in the pathways of ABA signal transduction and flavonoid biosynthesis, but not in the pathway of glycyrrhizic acid biosynthesis. Our study concludes that salt stress might promote liquiritin accumulation through the ABA-mediated signaling pathway, and provides effective reference for genetic improvement and comprehensive utilization of G. uralensis .

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Task-related functional magnetic resonance imaging-based neuronavigation for the treatment of depression by individualized repetitive transcranial magnetic stimulation of the visual cortex - Zhijun Zhang; Hongxing Zhang; Chun-Ming Xie; Meng Zhang; Yachen Shi; Ruize Song; Xiang Lu; Haisan Zhang; Kun Li; Bi Wang; Yongfeng Yang; Xianrui Li; et al. (Science China Life Sciences, 2021)

Photosynthetic properties and biochemical metabolism of Cucurbita moschata genotypes following infection with powdery mildew - Bi-Hua Chen; Wei-Li Guo; He-Lian Yang; Qing-Fei Li; Jun-Guo Zhou; Xin-Zheng Li (Journal of Plant Pathology, 2020)
Powdery mildew (PM) is one of the most important fungal diseases in Cucurbita moschata (pumpkin) cultivation. This experiment was conducted to shed light on the physiological mechanisms of PM resistance in pumpkin cultivars. PM pathogen was inoculated on pumpkin seedlings, PM-susceptible genotype (JJJD) and PM-resistant genotype (inbred line 112–2) to study the PM-fungal growth, plant photosynthetic and biochemical parameters with different intervals of time. The disease index and pathogen growth observed for the PM-infected 112–2 seedlings were milder than those observed for the JJJD seedlings. The net photosynthetic rate (Pn), stomatal conductance (gs) and transpiration rate (Tr) were reduced for both the PM-infected genotypes, while the internal CO 2 concentration (Ci) increased in comparison with the non-infected controls. PM pathogen inoculation impaired the photosynthetic performance in seedlings of both genotypes and this was largely associated with stomatal closure. In comparison with the non-infected controls, the superoxide dismutase (SOD) and β-1,3-glucanase activities were reduced for both the PM-infected genotypes, while the peroxidase (POD) and phenylalanine ammonia lyase (PAL) activities were increased. The catalase (CAT) activity was reduced in the 112–2 genotype and increased in the JJJD genotype after PM pathogen inoculation. Together, our data show that PM resistance in pumpkin seedlings is associated with the maintenance of photosynthetic performance and the regulation of defense-related enzyme activities .

Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Wu-Shan Dong; Peng-Fei Liu; Yu Liu; Yu Du; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2020)

Two new quinolone alkaloids from the nearly ripe fruits of Tetradium ruticarpum - Yi-Heng Li; Xiao Liu; Min Yin; Fei Liu; Bi Wang; Xu Feng; Qi-Zhi Wang (Natural Product Research, 2020)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Study on location allocation of earthquake emergency service depot based on hybrid multi-attribute decision making - Xianjun Guan; Fei Bi; Min Liu; Huayou Chen; Ligang Zhou (Natural Hazards, 2018)

Combined effects of soil heterogeneity, herbivory and detritivory on growth of the clonal plant Hydrocotyle vulgaris - Lu Liu; Peter Alpert; Bi-Cheng Dong; Jun-Min Li; Fei-Hai Yu (Plant and Soil, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Identification and Efficiency of a Nitrogen-fixing Endophytic Actinobacterial Strain from Sugarcane - Zhen Wang; Manoj Kumar Solanki; Fei Pang; Rajesh Kumar Singh; Li-Tao Yang; Yang-Rui Li; Hai-Bi Li; Kai Zhu; Yong-Xiu Xing (Sugar Tech, 2017)

Antioxidant activity of alcohol aqueous extracts of Crypthecodinium cohnii and Schizochytrium sp. - Jin-hui Yu; Yu Wang; Jie Sun; Fei Bian; Gao Chen; Yan Zhang; Yu-ping Bi; Ying-jie Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Association Between Osteopontin Gene Polymorphisms and Cerebral Palsy in a Chinese Population - Qing Shang; Chongchen Zhou; Dongzhi Liu; Wenxia Li; Mingjie Chen; Yiran Xu; Fei Wang; Dan Bi; Xiaoli Zhang; Xinzhi Zhao; Lei Wang; Changlian Zhu; et al. (NeuroMolecular Medicine, 2016)

Characterization of the relationship between vascular bundles features and indica-allelic frequency using a seventh filial generations of indica × japonica rice crosses - Tiansheng Liu; Wenjing Bi; Jia Zhang; Yue Cui; Zhiqiang Yan; Yuanzheng Wang; Cheng Fei; Hai Xu; Liang Tang; Wenfu Chen; Jian Sun; Quan Xu (Euphytica, 2016)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Clonal integration in homogeneous environments increases performance of Alternanthera philoxeroides - Bi-Cheng Dong; Peter Alpert; Qian Zhang; Fei-Hai Yu (Oecologia, 2015)

Enhanced adsorptive removal of selected pharmaceutical antibiotics from aqueous solution by activated graphene - Fei Yu; Jie Ma; Dongsu Bi (Environmental Science and Pollution Research, 2015)

The Banana MaLBD (LATERAL ORGAN BOUNDARIES DOMAIN) Transcription Factors Regulate EXPANSIN Expression and Are Involved in Fruit Ripening - Liang-jie Ba; Wei Shan; Jian-fei Kuang; Bi-hong Feng; Yun-yi Xiao; Wang-jin Lu; Jian-ye Chen (Plant Molecular Biology Reporter, 2014)

Enhanced transesterification of ethyl ferulate with glycerol for preparing glyceryl diferulate using a lipase in ionic liquids as reaction medium - Shangde Sun; Fei Qin; Yanlan Bi; Jingnan Chen; Guolong Yang; Wei Liu (Biotechnology Letters, 2013)

Scalar Flux–Gradient Relationships Under Unstable Conditions over Water in Coastal Regions - Zhongkuo Zhao; Zhiqiu Gao; Dan Li; Xueyan Bi; Chunxia Liu; Fei Liao (Boundary-Layer Meteorology, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Molybdenite Re–Os and muscovite 40Ar/39Ar dating of quartz vein-type W–Sn polymetallic deposits in Northern Guangdong, South China - Hua-Wen Qi; Rui-Zhong Hu; Xiao-Fei Wang; Wen-Jun Qu; Xian-Wu Bi; Jian-Tang Peng (Mineralium Deposita, 2012)

Effects of fragmentation on the survival and growth of the invasive, clonal plant Alternanthera philoxeroides - Bi-Cheng Dong; Peter Alpert; Wei Guo; Fei-Hai Yu (Biological Invasions, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Application of seismic anisotropy fluid detection technology in the Ken 71 well block of Shengli Oilfield - Li-Fei Bi; Zhong-Ping Qian; Feng Zhang; Xiao-Yan Chen; Shi-Chun Han; Mark Chapman (Applied Geophysics, 2011)

Effect of atmospheric aerosol on surface ozone variation over the Pearl River Delta region - XueJiao Deng; XiuJi Zhou; Dui Wu; XueXi Tie; HaoBo Tan; Fei Li; XueYan Bi; Tao Deng; DeHai Jiang (Science China Earth Sciences, 2011)

How internode length, position and presence of leaves affect survival and growth of Alternanthera philoxeroides after fragmentation? - Bi-Cheng Dong; Guo-Lei Yu; Wei Guo; Ming-Xiang Zhang; Ming Dong; Fei-Hai Yu (Evolutionary Ecology, 2010)

A study of perfectly matched layers for joint multicomponent reverse-time migration - Qi-Zhen Du; Rui-Yan Sun; Tong Qin; Yi-Tong Zhu; Li-Fei Bi (Applied Geophysics, 2010)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

Long-term culture of keratinocyte-like cells derived from mouse embryonic stem cells - Hai-Jun Huang; Qi-Shuang Gao; Bi-Fei Tao; Si-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2008)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Fluorescence Enhancement and Photostability of Novel Pentamethine Cyanines in Nafion-Na+ Membranes - Jing-Qu Guan; Zhi-Fei Dai; Chen-Ho Tung; Bi-Xian Peng (Journal of Fluorescence, 2000)